Advanced lithium–sulfur batteries enabled by a SnS2-Hollow carbon nanofibers Flexible Electrocatalytic Membrane. (30th October 2021) - Wei, Chengbiao; Han, Yulan; Liu, Hao; Gan, Ruihui; Li, Qiqi; Wang, Yali; Hu, P.; Ma, Chang; Shi, Jingli
Abstract: As emerging energy storage systems, lithium-sulfur (Li–S) batteries have engaged extensive attention owing to the ideal energy density. The bottleneck of achieving the practical application on Li–S batteries is the shuttle effects of lithium polysulfide (LiPS) and the sluggish electrochemical conversion kinetics. Here, a flexible SnS2 -hollow carbon nanofibers (SnS2 @HCNF) membrane is designed as an interlayer to catalyze the conversion of LiPS. Hollow carbon nanofibers (HCNF) provide an electron passageway to accelerate the redox reaction of LiPS, while SnS2 achieves rapid Li ions transport and an efficient catalytic route, promoting the decomposition of Li2 S. Owing to the synergistic effect of HCNF and SnS2, the SnS2 @HCNF endow the Li–S batteries with high rate performance (694 mAh g −1 at 3C) and low capacity fading rate (0.056 % per cycle during 500 cycles at 1C). The material and design strategy manifested in this work can pave a new way towards developing shuttle suppression interlayers. Graphical abstract: Image 1 Highlights: A Flexible Electrocatalytic Membrane of SnS2 -hollow carbon nanofibers (SnS2 @HCNF) is presented. The SnS2 @HCNF synergistically combined the advantages of high conductivity network and high electrocatalytic activity. The Li-S batteries with SnS2 @HCNF interlayer achieve outstanding rate performance and cycling stability.